Synthesis and selective tumor targeting properties of water soluble porphyrin-Pt(II) conjugates - Song, R; Kim, YS; Sohn, YS (ELSEVIER SCIENCE INC, 2002)
We have designed and synthesized a series of novel water soluble porphyrins and their platinum(11) conjugates, cis-[(Por)Pt(dmso)X], where Por=5-(4-pyridyl)-10,15,20-tris(4-sulfonatophenyl)porphyrin) (PyTPPS) or 5-[4-(3-aminopropyl)pyridiniumyl]-10,15,20-tris(4-sulphonatophenyl)porphyrin (PyTPPS-NPn), X = 2Cl, 1,1-cyclobutanedicarboxylic acid, oxalate, or malonate. Their biodistribution in tumor bearing mouse was examined along with their antitumor activity against murine leukemia L1210 cell line. The representative complex I exhibited a significant accumulation in tumor tissue with a tumor/muscle ratio of 7 after 24 It post injection. The antitumor activity of the title compounds was marginal (TIC: 95-117%), but it was found that platinum(II) coordination to the porphyrin periphery did not affect the tumor accumulating properties of the porphyrin permitting further derivatization for efficient delivery of the Pull) antitumor agent. (C) 2001 Elsevier Science Inc. All rights reserved.
Keywords: PLATINUM(II) COMPLEXES; PHOTODYNAMIC THERAPY; ANTITUMOR-ACTIVITY; PHOTOSENSITIZERS; PHTHALOCYANINE; LOCALIZATION; LIGANDS; AGENTS; CELL